Fraud Pentagon and Fraudulent Financial Reporting: Evidence from Manufacturing Companies in Indonesia and Malaysia - Fathmaningrum, Erni Suryandari; Anggarani, Gupita (Journal of Accounting and Investment, 2021)
Research aims: This study aims to examine the influence of fraud pentagon concept on fraudulent financial reporting.Design/Methodology/Approach: This study’s population was manufacturingcompanies listed in Indonesia Stock Exchange and Malaysia Stock Exchange. 120 manufacturing companies in Indonesia and 118 manufacturing companies in Malaysia were involved as samples. The data analysis method used in this study is multiple linear regression.Research findings: The results showed that financial target, financial stability, quality of external auditor, external pressure, and nature of industry variables influenced fraudulent financial reporting. In contrast, personal financial need, ineffective monitoring, change in auditor, change in director, and frequent number of CEO’s pictures variables had no effect on fraudulent financial reporting. For Indonesia, it was found that financial target, financial stability, and the quality of external auditor influenced fraudulent financial reporting. While, in Malaysia, the results showed that financial stability, external pressure, and nature of industry variables influenced fraudulent financial reporting in Malaysia.Theoretical contribution/Originality: These results support the financial target and quality of external auditor hypothesis in Indonesia, financial stability hypothesis in Indonesia and Malaysia, external pressure and nature of industry hypotheses in Malaysia, stating that fraud pentagon factors affect fraudulent financial reporting. It is also proved that there are different levels of fraudulent financial reporting in Indonesia and Malaysia. Indonesia has fraudulent financial reporting cases higher than Malaysia.